Infanticide, Secular Justice, and Religious Debate in Early Modern Europe - Prosperi, Adriano (Brepols, 2016)
On 5 December 1709, in Bologna, Lucia Cremonini is accused of a terrible crime: the murder of her newborn son. This tragic episode, exhumed from the depths of time, is placed at the centre of an enthralling study by one of the leading scholars of modern history and the history of religious beliefs. During the course of a dramatic trial the crime is debated by representatives of religious, philosophical, moral, and scientific culture, all characteristic of the formative period of the modern world and all seeking a convincing answer to fundamental questions. When does life begin? When can a human being first be described as such, so that his or her killing is a crime punishable by the maximum penalty? What is the true role of baptism in the formation of the human person? These are all highly topical questions in an age like our own, where belief is subject to the powerful assaults of scientific research and new questions are being raised about the essence and the limits of human existence. <span class=